Characteristics and Mental Health of Hispanic Dementia Caregivers in New York City. (September 2015) - Luchsinger, José A.; Tipiani, Dante; Torres-Patiño, Gabriela; Silver, Stephanie; Eimicke, Joseph P.; Ramirez, Mildred; Teresi, Jeanne; Mittelman, Mary
Background: Dementia prevalence and related caregiving burden are increasing, particularly among Hispanics. We studied the characteristics and mental health of Hispanic caregivers in New York City. Methods: We recruited 139 Hispanic family caregivers. We collected data on sociodemographic characteristics and predictors of caregiver burden, measured with the Zarit Caregiver Burden Scale, and depressive symptoms, measured with the Geriatric Depression Scale. Results: The mean age was 59.3 ± 10.4 years. The majority of caregivers were daughters and earned less than US30 000 a year. In multivariate analyses with linear regression, lower satisfaction with social networks was associated with higher caregiver burden and a greater number of depressive symptoms. Higher dementia severity was associated with higher caregiver burden, while higher caregiver comorbidities were associated with higher depressive symptoms. Conclusions: Caregiver comorbidities and satisfaction with social support may be targets for intervention that could improve caregiver burden and depressive symptoms among Hispanic caregivers.